Indoor air quality assessment in Klang Valley public hospitals: A proposal to improve Malaysian hospitals IAQ standard / Muhammad Iqbal Masri - Muhammad Iqbal , Masri (2018)
Air quality and clean air are important requirements that always been given higher priority in public health issue. It is become more important when it involves sensitive working environment such as hospitals which exposes high risk to staff, patients and visitors. Therefore, it is crucial for the hospital to put indoor air quality into concerns in particular. This study aims to investigate the distribution and pattern of Indoor Air Quality (IAQ) within selected Klang Valley hospitals. Besides that, this study also aims to evaluate the potential risk of the hospitals’ IAQ to the exposed healthcare workers. Three selected hospitals in Klang Valley were chosen for this cross sectional study. The study comprises of three phases. The first phase is walkthrough inspection where it was conducted prior the site assessment to check the room conditions and environment based on observation. The second phase is an experimental and quantitative phase where a structured IAQ assessments has been conducted at the selected hospitals which cover physical, chemical and biological parameters. The parameters reading were collected and compared to our national IAQ standard. The third phase is a qualitative phase where IAQ questionnaire responses were collected from the healthcare providers based on convenient sampling, aims to collect information on any IAQ related diseases signs and symptoms encountered. The data collected was analyzed using various association tests by using Statistical Package for Social Sciences (SPSS). It was found that during walkthrough inspection, poor housekeeping and maintenance issues at the Air Handling Unit rooms were one of the major issues identified. Generally, the main IAQ issues found were high relative humidity, low temperature and low air movement in all sampling areas. TVOC is below the recommended standard (<3) with reading of <0.01ppm at all locations. There is a concern on carbon dioxide (792ppm – 955ppm) and carbon monoxide (0.5ppm – 1.5ppm) concentration where it was detected in dental laboratory in all three hospitals. The IAQ assessment has recorded that majority of the hospitals has low temperature (19.8oC - 30.2oC), below the Indoor Air Quality Codes of Practice (ICOP), 2010 standard (23oC - 26oC). It was also found that the majority of the area sampled has exceed the relative humidity recommended by the standard (40% - 70%) ranging from 60% to 83.5%. Lastly, low air movement (m/s) was also found where the reading were below the recommended standard between 0.15m/s to 0.50m/s. The demographic of the respondents are 65.6% were female, 77.9% were in the age of 26 to 39 years old, 90.2% were not smoking, 67.5% were working less than 5 years and 84.7% were working in enclosed room type workstation. It was found that majority of the staff with 86% responses claim that the workstation is too cold and agreed that sometimes they experienced drowsiness (78%), fatigue (75%) and headache (74%). A comprehensive action plan covering immediate and preventive action plan is needed where it focuses on improving housekeeping practices and continuous indoor air quality monitoring are needed.